Enzymatic production of biosurfactants - de Carvalho, Ana Karine F.; Bento, Heitor B.S. [UNESP]; Carlos, Felipe R.; Hidalgo, Vitor B.; Romero, Cintia M.; Gambarato, Bruno C.; Da Rós, Patrícia C.M. (Wiley, 2023)
Surfactants produced by an enzymatic route are similar biomolecules to those surfactants obtained synthetically. Various enzymes sources that have been studied for surfactant production, such as amylases, glucosidases, and lipases. Biosurfactants show good properties and their applications have been increased in different areas including the cosmetic and healthcare industries and have also been applied as bioremediation agents. This chapter aims to describe and discuss biosurfactants produced by enzymatic routes. The production in a biorefinery context with the utilization of low-cost materials and also the use of techniques such as enzyme immobilization may contribute to the feasibility of the bioprocess. The use of a bioreactor also contributes to the increase in productivity. The use of enzymatically produced biosurfactants collaborates with the development of further sustainable industrial processes.
Keywords: Biocatalysts; Bioreactor; Enzymatic route; Esterification; Lipases